A práxis educativa do movimento dos trabalhadores rurais sem terra (MST): desafios e possibilidades no diálogo com instituições universitárias - Sonia Maria Roseno (2014)
The present study had as objective investigates the course of the educational praxis of MST in their partnerships with two teaching institutions: UFMG and UNESP. We analyzed how the specificity of organizational and formative way of MST it is dialoguing with the formation developed in the university and how this process it echoes in the praxis of the Movement that looks for to reach the formation of the Organic Intellectual: Educators, Militants who works the capacitation since the Childhood Education, Basic Education, EJA (Portuguese acronym for youth and adult education), Medium and walking for Higher Education. We identified how the organizational dynamics enabled apprehend the being while educator and at the same time while militant. We evidenced that the insert of the subjects in MST provides identities traits that configure them as collective subjects wherever they are inserted, in all of the learning processes (FREIRE, 1970, CASTELLS; 1999). Once centrality of formation in the Movement lies in the struggle for land, considered by many authors as a 'locus' generator of the Field Education (KOLLING, 1999).Leaving of the understanding that the methodological choice needs to identify with researcher and the object of the research, like this, we made the choice by MHD, for we consider that it more approaches with the methodological proposal to understand the praxis formative and educational of the Movement in their several determinations, contradictions and totality inside of the fight of classes (THOMPSON, 1987; MARX & ENGELS, 1974). The research was accomplished with four subjects alumnus of the Degree courses, among the partnership with the Landless Rural Workers Movement (MST - acronym in Portuguese), the Federal University of Minas Gerais (UFMG) through the Course of Degree in Education of the Field, and the University State from São Paulo "Júlio de Mesquita Filho" Campus Presidente Prudente, (UNESP) through the Course of Geography and with two leaderships of the national instances of MST. In the results we considered that the materialization of the internal organicity revealed us that doesn't import the place that these people are. The same ones possess an own way to interrelate with other subjects and with new spaces. In this sense we concluded the analysis not with a final point, but with countless considerations in understanding the formative and educational praxis of MST, in their 30 years and their partnerships.